Oxygen-containing acid radical chloride solid electrolyte as well as preparation method and application thereof
By introducing oxygenate ions into the chloride solid electrolyte, the formation of oxygenate chloride solid electrolytes has been solved, and the existing chloride solid electrolytes are insufficient electrochemical stability under high pressure is improved, and the conductivity and electrochemistry of lithium ion are improved Stability, achieving high capacity and high voltage all-solid state battery.
Patent Information
- Application Number
- CN202411565472.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-18
AI Technical Summary
The existing chloride solid electrolytes have insufficient electrochemical stability under high voltage and have low lithium ion conductivity, which limits the performance of all-solid state batteries.
The oxylate ions are introduced into the chloride solid electrolyte to form the oxylate chlorine solid electrolyte, which improves its lithium ion conductivity and thermodynamic stable potential.
The lithium ion conductivity and electrochemical stability of chloride solid electrolyte are improved, so that the high-voltage positive electrode/electrolyte interface can stabilize lithium ions at 4.5V, achieving a high-capacity and high-voltage all-solid-state battery.
Smart Images

Figure HDA0005119113480000011 
Figure HDA0005119113480000012 
Figure HDA0005119113480000013
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of solid-state batteries, and in particular relates to a type of oxygen-containing acid radical chloride solid electrolyte and a preparation method and application thereof. Background Art
[0002] With the continuous progress of human society, the relationship between energy utilization and environmental protection is becoming increasingly close. In recent years, the rapid development of renewable energy such as solar energy, wind energy and marine energy has brought opportunities for energy transformation, and rechargeable batteries as energy storage devices have also entered a stage of rapid growth. Among them, lithium-ion batteries are widely regarded as ideal clean energy because of their small size, light weight, long service life, low maintenance cost and high energy density. However, the organic electrolytes currently used in traditional lithium-ion batteries have safety hazards such as flammability and easy leakage. Therefore, there is an urgent need for safer lithium-ion conductive media to replace traditional electrolytes. In this context, solid-state electrolytes with the advantages of low flammability, high thermal stability, no leakage and low explosion risk have received widespread attention. So far, only a few solid-state electrolytes can achieve an ionic conductivity of 10 -3 S cm -1 level, including oxide, sulfide and chloride electrolytes. Among them, oxide solid electrolytes have high oxidation stability and good chemical stability, but their disadvantages such as low ionic conductivity and high solid-solid interface impedance limit their commercial progress; although sulfide solid electrolytes perform well in lithium ion conductivity and flexibility, they are extremely sensitive to humid air and have a narrow electrochemical window, making them incompatible with high-voltage positive electrode materials and lithium metal negative electrodes. In contrast, chloride solid electrolytes combine the advantages of oxide and sulfide electrolytes, with high ionic conductivity, high voltage stability (~4V) and good flexibility, and therefore receive increasing attention.
[0003] However, the chloride solid electrolytes reported in the literature often contain relatively rare and expensive rare earth elements such as Y, In, Sc, etc., which hinders their sustainable use in practical batteries. Therefore, the synthesis of low-cost and high-ionic conductivity chloride solid electrolytes has become a major research challenge. Recently, LiCl and ZrCl 4 Li prepared as raw material 2 ZrCl 6 Solid-state electrolytes have attracted widespread attention. However, their lithium ion conductivity still has room for improvement. In addition, the electrolyte will decompose at a voltage exceeding 4.2V, limiting the performance of all-solid-state batteries.
[0004] Therefore, further improving chloride solid electrolytes to enhance their lithium ion conductivity and electrochemical stability is an important direction for future research. Summary of the invention
[0005] In view of the defects of the prior art, the present invention provides a class of oxygen-containing acid chloride solid electrolytes. The present invention introduces oxygen-containing acid ions into the chloride solid electrolyte, which not only improves the lithium ion conductivity of the chloride solid electrolyte, but also improves its thermodynamically stable potential, so that the high-voltage positive electrode / electrolyte interface can stably transmit lithium ions at 4.5V, thereby obtaining a high-capacity and high-voltage all-solid-state battery.
[0006] The oxygen-containing acid radical chloride solid electrolyte provided by the present invention has a chemical formula as shown in formula (I):
[0007] xLiCl·yA·zB(Ⅰ)
[0008] Where A is ZrCl 4 、TaCl 5 , HfCl 4 、NbCl 4 、FeCl 3 、AlCl 3 One or more of; B is Li 2 MoO 4 , Li 2 WO 4 , Li 2 B 4 O 7 , Li 2 SO 4 、LiNO 3 , Li 2 CO 3 One or more of the following; 0.1≤x≤1.9; 0.8≤y≤1.2; 0.05 <z≤0.6。
[0009] Preferably, 0.4≤x≤1.4, 0.9≤y≤1.1; 0.1≤z≤0.4;
[0010] More preferably, x is 0.8 to 1.0 or 1.0 to 1.2; y is 0.9 to 1.0 or 1.0 to 1.1; and z is 0.1 to 0.3 or 0.3 to 0.4.
[0011] According to one embodiment of the present invention, the oxygen-containing chloride solid electrolyte is 0.8LiCl-ZrCl 4 -0.4Li 2 MoO 4 .
[0012] According to another embodiment of the present invention, the oxygen-containing chloride solid electrolyte is 0.8LiCl-ZrCl 4 -0.5Li 2 MoO 4 .
[0013] According to another embodiment of the present invention, the oxygen-containing chloride solid electrolyte is 1.2LiCl-ZrCl 4 -0.2Li 2 MoO 4 .
[0014] According to another embodiment of the present invention, the oxygen-containing chloride solid electrolyte is 0.8LiCl-ZrCl 4 -0.4Li 2 WO 4 .
[0015] According to another embodiment of the present invention, the oxygen-containing chloride solid electrolyte is 0.8LiCl-ZrCl 4 -0.6Li 2 WO 4 .
[0016] According to another embodiment of the present invention, the oxygen-containing chloride solid electrolyte is 1.1LiCl-ZrCl 4 -0.4Li 2 WO 4 .
[0017] According to another embodiment of the present invention, the oxygen-containing chloride solid electrolyte is 1.1LiCl-ZrCl 4 -0.35Li 2 WO 4 .
[0018] According to another embodiment of the present invention, the oxygen-containing chloride solid electrolyte is 1.4LiCl-ZrCl 4 -0.25Li 2 WO 4 .
[0019] The oxygen-containing acid radical chloride solid electrolyte of the present invention also contains [MoO 4 ] 2- or [WO 4 ] 2- or [B 4 O 7 ] 2- or [SO 4 ] 2- or [NO 3 ] 1- or [CO 3 ] 2- ions and chloride ions, the ionic conductivity of which is greater than or equal to 2×10 -4 S cm -1 Its electrochemical window is 0~5V (relative to Li + / Li electrode).
[0020] The present invention also provides a method for preparing the above oxygen-containing acid radical chloride solid electrolyte.
[0021] The preparation method of the oxygen-containing acid radical chloride solid electrolyte provided by the present invention includes the following two methods:
[0022] Method 1:
[0023] (1) firstly, according to the stoichiometric ratio of elements in the oxygen-containing acid chloride solid electrolyte, a Li-containing chloride and a metal chloride A are mixed and then ball-milled to obtain a chloride solid electrolyte;
[0024] (2) Then, according to the stoichiometric ratio of the oxygen-containing acid radical ions, the oxygen-containing acid radical lithium salt B is added to the chloride solid electrolyte and ball milled to obtain the result.
[0025] Method 2: According to the stoichiometric ratio of each element, the chloride containing Li, the metal chloride A, and the lithium salt B containing oxygen acid radical are mixed and then ball-milled to obtain the product.
[0026] In the above preparation method, the Li-containing chloride is LiCl; the metal chloride A is ZrCl 4 、TaCl 5 , HfCl 4 、NbCl 4 、FeCl 3 、AlCl 3 One or more of the following;
[0027] The lithium salt containing oxygen acid radical is Li 2 MoO 4 , Li 2 WO 4 , Li 2 B 4 O 7 , Li 2 SO 4 、LiNO 3 , Li 2 CO 3 One or more of the .
[0028] In the above preparation method, the ball milling conditions are as follows: the rotation speed is 300 to 1000 rpm, preferably 400 to 500 rpm; the time is 10 to 80 hours, preferably 30 to 60 hours.
[0029] In the above preparation method, the weighing and ball milling process is carried out in an atmosphere free of water and / or oxygen, such as an argon atmosphere.
[0030] The present invention also provides application of the above oxygen-containing acid radical chloride solid electrolyte.
[0031] The application of the oxygen-containing acid radical chloride solid electrolyte provided by the present invention is its application in preparing solid-state batteries.
[0032] Based on the oxygen-containing acid radical chloride solid electrolyte, the present invention also provides a composite positive electrode material.
[0033] The composite positive electrode material is composed of the oxygen-containing acid radical chloride solid electrolyte, positive electrode active material and conductive agent.
[0034] Furthermore, the positive electrode active material is LiFePO 4 、LiCoO 2 、LiNiO 2 、LiMn 2 O 4 、LiNi 0.8 Co 0.1 Mn 0.1 O 2 and LiNi 0.92 Co 0.03 Mn 0.05 O 2 One or more of the following;
[0035] Further, the conductive agent is one or more of Super-P, superconducting carbon black, acetylene black and Ketjen black;
[0036] Furthermore, the mass ratio of the oxygen-containing acid chloride solid electrolyte, the positive electrode active material and the conductive agent is 90-70:10-30:1-6, and the preferred mass ratio is 80:20:2.
[0037] According to an embodiment of the present invention, the composite positive electrode is composed of positive electrode material NM92, oxygen acid chloride solid electrolyte 0.8LiCl-ZrCl 4 -0.4Li 2 MoO 4 It is composed of conductive agent Super-P in a mass ratio of 80:20:2.
[0038] The present invention also provides a method for preparing the composite positive electrode material, comprising the following steps: mixing the oxygen-containing acid radical chloride solid electrolyte, positive electrode active material and conductive agent in proportion and then grinding or ball milling to obtain the composite positive electrode material.
[0039] Based on the oxygen-containing acid radical chloride solid electrolyte, the present invention also provides an energy storage element.
[0040] The energy storage element comprises the oxygen-containing acid radical chloride solid electrolyte.
[0041] Furthermore, the energy storage element is a solid-state battery.
[0042] The invention also provides a solid-state battery.
[0043] The solid-state battery comprises a positive electrode, a solid electrolyte and a negative electrode;
[0044] The solid electrolyte is the oxygen-containing acid chloride solid electrolyte, or a combination of the oxygen-containing acid chloride solid electrolyte and the sulfide solid electrolyte, and the preferred mass ratio of the two is 1: (1-3);
[0045] The sulfide solid electrolyte is preferably Li 6 PS 5 Cl;
[0046] The positive electrode is preferably the composite positive electrode material;
[0047] The negative electrode is preferably any one of metal Li, Li-In alloy and Si.
[0048] The present invention also provides a method for preparing the solid-state battery, comprising the following steps:
[0049] First, the solid electrolyte is pressed into a solid electrolyte sheet (such as a round sheet with a diameter of 10 mm), and then the composite positive electrode material is added to one side of the solid electrolyte sheet and pressurized (2 to 5 T) to form a positive electrode, and the negative electrode material is added to the other side and pressurized (0.5 to 2.5 T) to form a negative electrode, to obtain the solid-state battery.
[0050] The above assembly processes are all carried out under water-free (<0.1 ppm) and oxygen-free (<0.1 ppm) conditions, such as in a glove box.
[0051] When the solid electrolyte is a composition of an oxygen-containing acid chloride solid electrolyte and a sulfide solid electrolyte, the solid electrolyte consists of an oxygen-containing acid chloride solid electrolyte layer and a sulfide solid electrolyte layer, the oxygen-containing acid chloride solid electrolyte layer in the solid electrolyte is in direct contact with the positive electrode, and the sulfide solid electrolyte layer in the solid electrolyte is in direct contact with the negative electrode.
[0052] The present invention obtains the oxygen-containing acid radical chloride solid electrolyte by partially replacing chloride ions with oxygen-containing acid radical ions. This behavior not only effectively improves the lithium ion conductivity of the chloride solid electrolyte (>10 -4 S cm -1), and at the same time, the thermodynamically stable potential of the electrolyte is increased. The interface of this type of solid electrolyte / high-voltage positive electrode is stable under high voltage (4.5V), and the preparation method of this type of oxygen-containing acid chloride solid electrolyte is simple, the raw material cost is low, and it is conducive to large-scale production, which broadens the application prospects of this type of solid electrolyte. BRIEF DESCRIPTION OF THE DRAWINGS
[0053] Figure 1 The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 1 of the present invention 4 -0.4Li 2 MoO 4 Scanning electron microscope (SEM) test results.
[0054] Figure 2 The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 1 of the present invention 4 -0.4Li 2 MoO 4 X-ray energy dispersive spectrum analysis (EDS) test results.
[0055] Figure 3 The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 1 of the present invention 4 -0.4Li 2 MoO 4 X-ray diffraction (XRD) test results.
[0056] Figure 4 The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 1 of the present invention 4 -0.4Li 2 MoO 4 Electrochemical impedance spectroscopy (EIS) test results.
[0057] Figure 5 The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 1 of the present invention 4 -0.4Li 2 MoO 4 The charge and discharge curves.
[0058] Figure 6 The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 4 of the present invention 4 -0.4Li 2 WO 4 Electrochemical impedance spectroscopy (EIS) test results.
[0059] Figure 7The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 4 of the present invention 4 -0.4Li 2 WO 4 Scanning electron microscope (SEM) test results.
[0060] Figure 8 The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 4 of the present invention 4 -0.4Li 2 WO 4 X-ray energy dispersive spectrum analysis (EDS) test results.
[0061] Fig. 9 The solid electrolyte 0.8LiCl-ZrCl containing oxygen acid chloride in Example 4 of the present invention 4 -0.4Li 2 WO 4 X-ray diffraction (XRD) test results. DETAILED DESCRIPTION
[0062] The present invention is further described in detail below in conjunction with specific embodiments, and the examples provided are only for illustrating the present invention, rather than for limiting the scope of the present invention. The examples provided below can be used as a guide for further improvements by those of ordinary skill in the art, and do not constitute a limitation of the present invention in any way.
[0063] The experimental methods in the following examples, unless otherwise specified, are all conventional methods, and are performed according to the techniques or conditions described in the literature in the field or according to the product instructions. The materials, reagents, etc. used in the following examples, unless otherwise specified, can all be obtained from commercial channels.
[0064] Example 1: Oxygen-containing acid chloride solid electrolyte 0.8LiCl-ZrCl 4 -0.4Li 2 MoO 4 Preparation and performance testing
[0065] 1. Preparation of Oxygen-containing Acid Chloride Solid Electrolyte
[0066] In the glove box, accurately weigh LiCl and ZrCl in a molar ratio of 0.8:1:0.4. 4 and Li 2 MoO 4 In the ball mill, tighten the ball mill to make the ball mill in an inert gas atmosphere of argon. Ball mill at 450 rpm for 50 h to obtain the oxygen-containing chloride solid electrolyte 0.8LiCl-ZrCl 4 -0.4Li 2 MoO4 .
[0067] 2. Characterization of Oxygen-containing Acid Chloride Solid Electrolyte
[0068] The scanning electron microscope (SEM) image of the oxygen-containing acid chloride solid electrolyte prepared in this example is as follows: Figure 1 As shown, the X-ray energy spectrum analysis (EDS) diagram is as follows Figure 2 As shown in Figure 2, X-ray diffraction (XRD) Figure 3 As shown, it shows that Zr, Mo, O, and Cl elements are evenly distributed in the particles. Based on the above analysis, this example successfully obtained the oxygen-containing acid chloride solid electrolyte 0.8LiCl-ZrCl 4 -0.4Li 2 MoO 4 .
[0069] 3. Test of lithium ion conductivity
[0070] The prepared electrolyte powder was placed in a polytetrafluoroethylene mold with a diameter of 10 mm, and then an iron cylinder with a diameter of 10 mm was used to pressurize it up and down at 450 MPa for EIS test. The test results are as follows: Figure 4 As shown, the room temperature ionic conductivity is 0.2×10 -3 S cm -1 .
[0071] 3. Electrochemical performance test
[0072] 1. Oxygen-containing acid chloride solid electrolyte 0.8LiCl-ZrCl 4 -0.4Li 2 MoO 4 Preparation of composite cathode materials:
[0073] The positive electrode material NM92 and the solid electrolyte 0.8LiCl-ZrCl 4 -0.4Li 2 MoO 4 The conductive agent Super-P was weighed in a mass ratio of 80:20:2, mixed in an agate mortar, and ground for 30 minutes to mix the materials evenly to obtain a composite positive electrode material.
[0074] 2. Assembling solid-state batteries:
[0075] First add 70 mg of Li 6 PS 5 Cl was pressurized to 1T, followed by the addition of 30 mg of 0.8LiCl-ZrCl 4 -0.4Li 2 MoO 4Pressurize to 1T. Then on the positive electrode side (and 0.8LiCl-ZrCl 4 -0.4Li 2 MoO 4 Add 8 mg of composite positive electrode material to the side in contact with Li 6 PS 5 The Li-In alloy is added to the side that contacts Cl and pressurized to 1.5 T. The preparation process must be carried out in a glove box.
[0076] 3. Testing of solid-state batteries:
[0077] The test temperature is 25°C, the voltage range of the constant charge and discharge test is 2.4~3.9V, and the charge and discharge curve of the solid-state battery at 0.1C is as follows: Figure 5 As shown, it can be seen that the discharge specific capacity of the battery is 201 mAh / g.
[0078] Example 2: Preparation of 0.8LiCl-ZrCl Oxygen-containing Chloride Solid Electrolyte 4 -0.5Li 2 MoO 4
[0079] 1. Preparation of Oxygen-containing Acid Chloride Solid Electrolyte
[0080] The preparation steps are basically the same as those in Example 1, except that different molar mass ratios of raw materials are used.
[0081] 2. Test of lithium ion conductivity
[0082] The test conditions were basically the same as those in Example 1, and the ionic conductivity at room temperature was 0.3×10 -3 S cm -1 .
[0083] Example 3: Preparation of oxygen-containing acid chloride solid electrolyte 1.2LiCl-ZrCl 4 -0.2Li 2 MoO 4
[0084] 1. Preparation of Oxygen-containing Acid Chloride Solid Electrolyte
[0085] The preparation steps are basically the same as those in Example 1, except that different molar mass ratios of raw materials are used.
[0086] 2. Test of lithium ion conductivity
[0087] The test conditions were basically the same as those in Example 1, and the ionic conductivity at room temperature was 1×10 -3 S cm -1 .
[0088] Example 4: Oxygen-containing acid chloride solid electrolyte 0.8LiCl-ZrCl 4 -0.4Li 2 WO 4 Preparation and performance testing
[0089] 1. Preparation of Oxygen-containing Acid Chloride Solid Electrolyte
[0090] The preparation steps are basically the same as those in Example 1, except that: 2 MoO 4 Replace with Li 2 WO 4 .
[0091] 2. Test of lithium ion conductivity
[0092] The test conditions are basically the same as those in Example 1, and the test results are as follows: Figure 6 As shown, the room temperature ionic conductivity is 0.26×10 -3 S cm -1 .
[0093] 3. Characterization of Oxygen-containing Acid Chloride Solid Electrolytes
[0094] The scanning electron microscope (SEM) image of the oxygen-containing acid chloride solid electrolyte prepared in this example is as follows: Figure 7 As shown, the X-ray energy spectrum analysis (EDS) diagram is as follows Figure 8 As shown in Figure 2, X-ray diffraction (XRD) Fig. 9 As shown, it shows that Zr, W, O, and Cl elements are evenly distributed in the particles. Based on the above analysis, this example successfully obtained the oxygen-containing acid chloride solid electrolyte 0.8LiCl-ZrCl 4 -0.4Li 2 WO 4 .
[0095] Example 5: Preparation of 0.8LiCl-ZrCl Oxygen-containing Chloride Solid Electrolyte 4 -0.6Li 2 WO 4
[0096] 1. Preparation of Oxygen-containing Acid Chloride Solid Electrolyte
[0097] The preparation steps are basically the same as those in Example 4, except that different molar mass ratios of raw materials are used.
[0098] 2. Test of lithium ion conductivity
[0099] The test conditions were basically the same as those in Example 1, and the ionic conductivity at room temperature was 0.4×10 -3 S cm-1 .
[0100] Example 6: Preparation of oxygen-containing acid chloride solid electrolyte 1.1LiCl-ZrCl 4 -0.4Li 2 WO 4
[0101] 1. Preparation of Oxygen-containing Acid Chloride Solid Electrolyte
[0102] The preparation steps are basically the same as those in Example 4, except that different molar mass ratios of raw materials are used.
[0103] 2. Test of lithium ion conductivity
[0104] The test conditions were basically the same as those in Example 1, and the ionic conductivity at room temperature was 0.6×10 -3 S cm -1 .
[0105] Example 7: Preparation of oxygen-containing acid chloride solid electrolyte 1.1LiCl-ZrCl 4 -0.35Li 2 WO 4
[0106] 1. Preparation of Oxygen-containing Acid Chloride Solid Electrolyte
[0107] The preparation steps are basically the same as those in Example 4, except that different molar mass ratios of raw materials are used.
[0108] 2. Test of lithium ion conductivity
[0109] The test conditions were basically the same as those in Example 1, and the ionic conductivity at room temperature was 0.9×10 -3 S cm -1 .
[0110] Example 8: Preparation of Oxygen-containing Acid Chloride Solid Electrolyte 1.4LiCl-ZrCl 4 -0.25Li 2 WO 4
[0111] 1. Preparation of Oxygen-containing Acid Chloride Solid Electrolyte
[0112] The preparation steps are basically the same as those in Example 4, except that different molar mass ratios of raw materials are used.
[0113] 2. Test of lithium ion conductivity
[0114] The test conditions were basically the same as those in Example 1, and the ionic conductivity at room temperature was 1.5×10 -3 S cm-1 .
[0115] The present invention has been described in detail above. It will be apparent to those skilled in the art that the present invention may be implemented in a wide range under equivalent parameters, concentrations and conditions without departing from the spirit and scope of the present invention and without the need for unnecessary experimentation. Although the present invention provides specific embodiments, it should be understood that further improvements may be made to the present invention. In short, according to the principles of the present invention, this application intends to include any changes, uses or improvements to the present invention, including changes made by conventional techniques known in the art that depart from the scope disclosed in this application. Applications of some of the basic features may be made within the scope of the following appended claims.
Claims
1. An oxygen-containing acid chloride solid electrolyte, whose chemical formula is shown in formula (I): xLiCl·yA·zB(Ⅰ) in, A is one or more of ZrCl4, TaCl5, HfCl4, NbCl4, FeCl3, AlCl3; B is one or more of Li2MoO4, Li2WO4, Li2B4O7, Li2SO4, LiNO3, Li2CO3; 0.1≤x≤1.9; 0.8≤y≤1.2; 0.05 <z≤0.6。 2. The oxygen-containing acid radical chloride solid electrolyte according to claim 1, characterized in that: 0.4≤x≤1.4, 0.9≤y≤1.1; 0.1≤z≤0.
4.
3. The method for preparing the oxygen-containing acid radical chloride solid electrolyte according to claim 1 or 2, comprising the following two methods; Method 1 includes the following steps: (1) firstly, according to the stoichiometric ratio of elements in the oxygen-containing acid radical chloride solid electrolyte, a Li-containing chloride and a metal chloride A are mixed and then ball-milled to obtain a chloride solid electrolyte; (2) then adding the lithium salt B containing oxygen acid radicals to the chloride solid electrolyte according to the stoichiometric ratio of oxygen acid radical ions and performing ball milling to obtain the obtained product; Method 2 comprises the following steps: according to the stoichiometric ratio of each element, a chloride containing Li, a metal chloride A, and a lithium salt containing an oxygen acid radical B are mixed and then ball-milled to obtain the mixture.
4. The preparation method according to claim 3, characterized in that: The Li-containing chloride is LiCl; And / or, the metal chloride A is one or more of ZrCl4, TaCl5, HfCl4, NbCl4, FeCl3, and AlCl3; And / or, the lithium salt containing oxygen acid radical is one or more of Li2MoO4, Li2WO4, Li2B4O7, Li2SO4, LiNO3, and Li2CO3; And / or, the ball milling conditions are as follows: the rotation speed is 300 to 1000 rpm, preferably 400 to 500 rpm; the time is 10 to 80 hours, preferably 30 to 60 hours; And / or, the ball milling process is performed in an atmosphere free of water and / or free of oxygen.
5. Use of the oxoacid chloride solid electrolyte according to claim 1 or 2 in the preparation of solid-state batteries.
6. A composite positive electrode material, comprising the oxoacid chloride solid electrolyte according to claim 1 or 2, a positive electrode active material and a conductive agent.
7. The composite positive electrode material according to claim 6, characterized in that: The positive electrode active material is LiFePO4, LiCoO2, LiNiO2, LiMn2O4, LiNi 0.8 Co 0.1 Mn 0.1 O2 and LiNi 0.92 Co 0.03 Mn 0.05 One or more of O2; And / or, the conductive agent is one or more of Super-P, superconducting carbon black, acetylene black and Ketjen black; And / or, the mass ratio of the oxygen-containing acid chloride solid electrolyte, the positive electrode active material and the conductive agent is 90-70:10-30:1-6.
8. An energy storage element, comprising the oxygen-containing acid chloride solid electrolyte according to claim 1 or 2; Furthermore, the energy storage element is a solid-state battery.
9. A solid-state battery, comprising a positive electrode, a solid electrolyte and a negative electrode, characterized in that: The solid electrolyte comprises the oxygen-containing acid chloride solid electrolyte according to claim 1 or 2.
10. The solid-state battery according to claim 9, characterized in that: The solid electrolyte is the oxygen-containing acid chloride solid electrolyte, or a combination of the oxygen-containing acid chloride solid electrolyte and a sulfide solid electrolyte. Preferably, the mass ratio of the oxygen-containing acid chloride solid electrolyte to the sulfide solid electrolyte is 1:(1-3); And / or, the positive electrode is the composite positive electrode material; And / or, the negative electrode is any one of metal Li, Li-In alloy and Si.
11. The method for preparing a solid-state battery according to claim 9 or 10, comprising the following steps: first, pressing the solid electrolyte into a solid electrolyte sheet, then adding the composite positive electrode material to one side of the solid electrolyte sheet and pressurizing it to form a positive electrode, and adding the negative electrode material to the other side and pressurizing it to form a negative electrode, to obtain the solid-state battery.
12. The preparation method according to claim 11, characterized in that: The above assembly processes were all carried out under water-free (<0.1 ppm) and oxygen-free (<0.1 ppm) conditions.